Verification of North Atlantic warm conveyor belt outflowsin ECMWF forecasts. (10th October 2014) - Madonna, Erica; Boettcher, Maxi; Grams, Christian M.; Joos, Hanna; Martius, Olivia; Wernli, Heini
<x xml:space="preserve">Abstract</x> A feature‐based approach is introduced to assess the quality of the representation of warm conveyor belts (WCBs) in high‐resolution forecasts of the European Centre for Medium‐range Weather Forecasts (ECMWF). WCBs are moist ascending airstreams in extratropical cyclones, which transport boundary‐layer air within 1–2 days poleward to the upper troposphere. The WCB outflow is typically characterised by low potential vorticity (PV), amplifying upper‐level ridges and in turn modifying the jet stream and downstream Rossby wave evolution. Therefore the correct representation of WCBs can be essential for medium‐range weather prediction. A three‐component verification measure PAL is introduced, measuring errors in the WCB outflow's PV anomaly (P component), the amplitude of the WCB (A component), and the location of the outflow (L component). The PAL approach is applied to North Atlantic WCBs in ECMWF forecasts during three winters between 2002/2003 and 2010/2011. For the latest winter, the PAL results are also compared to the anomaly correlation coefficient (ACC) of upper‐level PV. It is shown that (i) the representation of WCBs improves for forecasts with a shorter lead time, (ii) PAL values are on average better for more recent forecasts, (iii) recent model versions show no systematic over‐ or underestimation of WCB intensity, (iv) individual medium‐range forecasts can be associated with large errors in particular in the amplitude of WCBs, and (v) the comparison of PAL and the ACC indicates that several poor forecasts in terms of ACC are indeed associated with significant errors in the representation of WCBs. Limitations of this study are also discussed.